2020
DOI: 10.1101/2020.07.02.184408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Complex DNA Rearrangements During Early Stages of HAC Formation

Abstract: AbstractHuman Artificial Chromosomes (HACs) are important tools for epigenetic engineering, for measuring chromosome instability (CIN) and possible gene therapy. However, their use in the latter is potentially limited because the input HAC-seeding DNA can undergo an unpredictable series of rearrangements during HAC formation. As a result, after transfection and HAC formation, each cell clone contains a HAC with a unique structure that cannot be precisely predicted from the stru… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Using transformationassociated recombination in yeast, it was shown that 2mer or 4mer or 5mer alphoid DNA repeats consisting of alphoid 170 bp monomers and having the ends homologous to each other may be one-step TARassembled into long synthetic alphoid DNA arrays varying in size from 50 to 140 kb (Step 1: Figure 11). After transfection of such arrays into human cells, de novo HACs are generated, ranging in size from 1 to 10 Mb due to amplification of the input alphoid DNA arrays (Steps 2 and 3) [139][140][141][142][143]. Because any nucleotide in the original dimer can be easily changed before its amplification, this TAR-based method allows to identify the critical regions of the alphoid repeat for de novo centromere seeding.…”
Section: Synthetic Biology: Construction Of Human Artificial Chromoso...mentioning
confidence: 99%
“…Using transformationassociated recombination in yeast, it was shown that 2mer or 4mer or 5mer alphoid DNA repeats consisting of alphoid 170 bp monomers and having the ends homologous to each other may be one-step TARassembled into long synthetic alphoid DNA arrays varying in size from 50 to 140 kb (Step 1: Figure 11). After transfection of such arrays into human cells, de novo HACs are generated, ranging in size from 1 to 10 Mb due to amplification of the input alphoid DNA arrays (Steps 2 and 3) [139][140][141][142][143]. Because any nucleotide in the original dimer can be easily changed before its amplification, this TAR-based method allows to identify the critical regions of the alphoid repeat for de novo centromere seeding.…”
Section: Synthetic Biology: Construction Of Human Artificial Chromoso...mentioning
confidence: 99%